The Influence of Adolescent Physical Activity on Bone Mineral Density among Adult Runners - Ikegami, Nodoka; Hatsukari, Akiko; Kamikubo, Toshinao; Yamamoto, Ryota; Tsutsui, Toshiharu; Torii, Suguru (International Journal of Sports Medicine, 2024)
This study aimed to determine the influence of sport type and training volume during adolescence on low bone mineral density (BMD) in long-distance runners. In total, 125 competitive long-distance runners (64 males; 21.3±4.2 years, 61 females; 21.4±3.1 years) participated in this retrospective cohort study. We collected training history data during adolescence using a questionnaire and measured BMD of the lumbar spine and whole body using dual-energy X-ray absorptiometry (DXA). Male runners with low BMD ran for more hours (p=0.02) and had a smaller proportion of multidirectional loading activity (p=0.03) in elementary school than those with normal BMD. Although female runners with low BMD performed multidirectional activity for more hours in middle school than those with normal BMD (p=0.01), running volume was similar between groups. There was an increasing trend in the total number of hours of physical activity in middle school in female runners with low BMD (p=0.05). These results suggest that avoiding specialization in long-distance running, increasing the proportion of multidirectional sports, and preventing overload during the bone growth phase may reduce the risk of low BMD among runners.
Keywords: bone health; bone stress injuries; impact loading; amenorrhea; overload